The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.cub.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Elasticity Regulates Lamin-A,C Phosphorylation and Turnover with Feedback to Actomyosin

Abstract: Summary Tissue microenvironments are characterized not only in terms of chemical composition but also by collective properties such as stiffness, which influences the contractility of a cell, its adherent morphology, and even differentiation [1–8]. The nucleoskeletal protein lamin-A,C increases with matrix stiffness, confers nuclear mechanical properties, and influences differentiation of mesenchymal stem cells (MSCs) [9]. Here we show in single cell analyses that matrix stiffness couples to myosin-II activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
385
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 333 publications
(423 citation statements)
references
References 35 publications
35
385
2
1
Order By: Relevance
“…Consistent with the results reported here indicating that cyclic stretch may posttranslationally regulate lamin A/C, a 40-kDa lower band of lamin A/C (Fig. S4) indicates cleavage of lamin A/C that is regulated by adhesion and cell mechanics, as shown by Buxboim et al (28). Furthermore, our current study demonstrates that, in addition to lamin A/C, the expression of emerin in VSMCs also is modulated by mechanical cyclic stretch and subsequently induces VSMC proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with the results reported here indicating that cyclic stretch may posttranslationally regulate lamin A/C, a 40-kDa lower band of lamin A/C (Fig. S4) indicates cleavage of lamin A/C that is regulated by adhesion and cell mechanics, as shown by Buxboim et al (28). Furthermore, our current study demonstrates that, in addition to lamin A/C, the expression of emerin in VSMCs also is modulated by mechanical cyclic stretch and subsequently induces VSMC proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that the cell can respond to the mechanical characteristics of its microenvironment by stabilizing lamin A/C and regulating changes in lamin protein composition and nuclear morphology (44). The timescale of this process is significantly slower than that of the perinuclear actin polymerization described in this study (tens of minutes vs. tens of seconds).…”
Section: Discussionmentioning
confidence: 51%
“…Third, inhibition of NMII activity affects the behavior of neural crest cells generated during neuroepithelial EMT in vivo in zebrafish brain development (Berndt et al, 2008). Moreover, fourth, NMII activity has been shown to affect stem cell lineage specification (Buxboim et al, 2014;Engler et al, 2006;Kim et al, 2015;Wang et al, 2012). All of these findings suggest that NMII may be involved in regulating epicardial EMT.…”
Section: Introductionmentioning
confidence: 72%